Substance P and Glucagon-like Peptide-17-36 Amide Mediate Anorexic Responses to Trichothecene Deoxynivalenol and Its Congeners - Jia, Hui; Qin, Zihui; Wei, Ben; Guo, Xinyi; Xiao, Huiping; Zhang, Huayue; Li, Zelin; Wu, Qinghua; Zheng, Ruibo; Wu, Wenda (Toxins, 2022)
Type B trichothecenes commonly contaminate cereal grains and include five structurally related congeners: deoxynivalenol (DON), 3-acetyldeoxynivalenol (3-ADON), 15-acetyldeoxynivalenol (15-ADON), fusarenon X (FX), and nivalenol (NIV). These toxins are known to have negative effects on human and animal health, particularly affecting food intake. However, the pathophysiological basis for anorexic effect is not fully clarified. The purpose of this study is to explore the potential roles of the brain-gut peptides substance P (SP) and glucagon-like peptide-17-36 amide (GLP-1) in anorexic responses induced by type B trichothecenes following both intraperitoneal (IP) and oral administration. SP and GLP-1 were elevated at 1 or 2 h and returned to basal levels at 6 h following exposure to DON and both ADONs. FX induced the production of both brain gut peptides with initial time at 1 or 2 h and duration > 6 h. Similar to FX, exposing IP to NIV caused elevations of SP and GLP-1 at 1 h and lasted more than 6 h, whereas oral exposure to NIV only increased both brain gut peptides at 2 h. The neurokinin-1 receptor (NK-1R) antagonist Emend® dose-dependently attenuated both SP- and DON-induced anorexic responses. Pretreatment with the GLP-1 receptor (GLP-1R) antagonist Exending9-39 induced a dose-dependent attenuation of both GLP-1- and DON-induced anorexic responses. To summarize, the results suggest that both SP and GLP-1 play important roles in anorexia induction by type B trichothecenes.
Keywords: brain-gut peptide; Appetite Depressants; trichothecene; Humans; Trichothecenes, Type B; glucagon-like peptide-17-36 amide; trichotheceny typu B; Anorexia; anorexia; Trichothecenes; Amides; lidé; trichotheceny; zvířata; glukagonu podobný peptid 1; anorektika; Glucagon-Like Peptide 1; Substance P; nechutenství; Animals; amidy; substance P